Skrining Golongan Senyawa Kimia dan Pengujian Aktivitas Antioksidan Ekstrak Ubijalar (Ipomoea batatas (L.)Lam.) Varietas Lokal di Distrik Skanto Kabupaten Keerom Provinsi Papua - Yuliana H. Rumsarwir; Linus Y. Chrystomo; Maklon Warpur (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
Sweet potato (Ipomoea batatas) is native plant comes from the American continent. It began to spread throughout the world, especially in the tropical countries in the 16th century. Papua Province is one of the regions with the largest area of harvested sweetpotato in Indonesia, therefore there is a high chance to develop food independence in Papua. Because of the Papuan people are accustomed consuming non-rice food. The study was conducted in the Biology Laboratory and the Pharmacy laboratory of MIPA Faculty Cenderawasih University and also the supporting Laboratory of The Papua Agricultural Research and Development Center (Balitbangtan). The purpose of this research is to test the quality of flour of Keerom sweet potato varieties. Method for flour of sweet potato quality testing were using phytochemical screening to determine the chemical compound group and using antioxidant test with the DPPH (1-diphenyl-2-picrylhydrazyl) method. The results of the description of the Skanto District Keerom sweet potatoes in the field were three (3) local varieties including Weayuken (purple sweet potato), Musanaken (yellow sweet potato) and Hiho (white sweet potato). The result of phytochemical screening show that the purple sweet potato variety has more chemical compounds consist of tannins, quinones, flavonoids, terpenoids and alkaloids compared to white sweet potato consist of alkaloids only and yellow sweet potato consist of tannins, flavonoids, terpenoids and alkaloids. The result of antioxidant activity tests to flour extract ethanol has IC50values of 299.82 ppm (purple sweet potato), 301.18 (yellow sweet potato), 1027.98 ppm (white sweet potato) respectively. So can be conclude that the purple sweet potato variety is the best. It was suggested for further research to isolate bioactive compounds and test antioxidants to other varieties in other centers areas of sweetpotato culture which have potential to develop for food, supplement and tradisional drugs.Key words: Sweet potato; local varieties; flour quality; phytochemical screening; antioxidant test